Correlation analysis of LPR-5, SOST and MHR with poor prognosis in patients with type 2 diabetes mellitus complicated with osteoporosis: LPR-5, SOST and MHR for fractures in osteoporosis with type 2 diabetes - Li, Xiang; Sun, Shiwei; Zhang, Tianlong; Li, Bohao; Zhang, Jiarui; Zhao, Yu; Xie, Yi; Yang, Siqi; Wang, Minghai (Journal of Medical Biochemistry, 2025)
Objective To evaluate the predictive value of the monocyte/high-density lipoprotein cholesterol ratio (MHR), low-density lipoprotein-associated protein (LRP)-5 and sclerosing protein (SOST) for fractures in patients with osteoporosis due to type 2 diabetes.Methods For the osteoporosis group, 218 individuals who received a type 2 diabetes diagnosis at this facility between January 2023 and December 2024 were chosen. Moreover, 90 patients with normal bone mass and 130 patients with decreased bone mass due to type 2 diabetes who were diagnosed at this center over the same time period were chosen as the normal bone mass group and the decreased bone mass group. Changes in the MHR, LPR-5 and SOST in each group and their relationships with the severity of fractures were observed. Binary logistic regression was used to analyze the influencing factors of fractures in patients with osteoporosis. Receiver operating characteristic (ROC) curves were used to assess the prediction effectiveness of the MHR, LPR-5, and SOST for fractures iin individuals with type 2 diabetes-related osteoporosis.Results In the osteoporosis group, the MHR and LPR-5 were substantially higher (P
Keywords: Type 2 diabetes; Osteoporosis; Fracture; Blood lipids; Hardened protein